(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2026)
According to UNESCO 2003 convention, Intangible cultural heritage (ICH) includes traditions, customs, and socio-cultural practices which forms an important part of cultural identity of cities. In many Indian historic cities, the interconnection of intangible assets with tangible heritage is not well studied. Nashik, a historic city in India, represents layers of natural, intangible cultural heritage and built heritage elements, but lacks empirical research on their relationship and how different generations perceive this relationship. With specific focus on identifying generational differences, the aim of the study is to investigate public perceptions of tangible-intangible relationship taking a case of Nashik, Maharashtra. A mixed methods approach is employed, where a qualitative projective survey in combination with a structured Likert-scale survey questionnaire is used to achieve the results. This study examines three themes: Sense of Identity and place attachment; Spatial-Built contributions to ICH; and Cultural practices as socially constructed. The findings indicate that urban heritage is perceived as more closely connected to intangible cultural heritage (ICH) than to natural heritage. The results also demonstrate that age groups significantly influence the variation in individuals’ perception of heritage assets which should be addressed in policy making decisions. This study informs grounded conservation strategies based on empirical evidence for better engagement in heritage management.